Palatability and nutrient utilization of different treatments of undigested rumen content in Black Bengal goats - GHOSH, T K; DEY, A; SENAPATI, P K (The Indian Journal of Animal Sciences, 2013)
Black Bengal nonpregnant does (35) of almost Same age and body weIght (68/kg) were divided into 5 equal groups to determine nutrient utilization, body weight gain and nutrient balance of feeds containing rumen contents in different combainations and forms. The control is provided with oat hay as roughage diet In all feed contained dried rumen content, urea and molassess; all the above ingredients were common but urea nitrogen was replaced by dried poultry droppings. In addition, all were given common concentrate mixture. The experiments were conducted for 180 days during which 2 metabolic trials, one at 180 day and other at 140 day with 10-day collection period were carried out. The DM intake was highest in control (T1) and lowest in T5 (p<0.01). Significant difference in acceptability of different combinations and forms of rumen content (P<0.05) and in body weight gain were also recorded. The OM, CF, EE, CP, OM and NFE digestibilities were found to differ significantly among groups. T3 group revealed highest digestibility of OCH, OCP and TON intakes. The balances of N, Ca and P were positive in all groups. Intake of N, Ca and P varied significantly (P<0.01) among groups, although retention did not follow same trend. The above observation suggests that nonsilage rwnen conteilt as a sole roughage diet can be used efficiently in goats.